State of stock-breeding in Ukraine - Mostenska, Tatyana; Tarasiuk, Galina; Shapran, Ludmila (My University, 2011)
The article is devoted to the analysis of the state of stock-breeding in Ukraine, namely the problems of cattle breeding, poultry husbandry, pig breeding and ways of competitive growth of livestock production.
Keywords: тваринництво; animal husbandry; cattle; велика рогата худоба; кафедра ділової іноземної мови та міжнародної комунікації; кафедра економіки праці та менеджменту